Competitividade das exportações de plantas vivas e produtos de floricultura do Ceará e do Brasil no período de 1998 a 2004 - Silva, Etevaldo Almeida (2006)
Brazil and particularly the state of Ceará have considerably increased the exports of live plants and flower-raising products and participated effectively em the opening of new boundaries to the country. Nevertheless, little is known about competitiveness in Brazilian and Ceará Exports, regarding other national exports. Thus, we have tried to identify what competitive performance Brazil and Ceará have in the international market of this segment. In order to accomplish this, the following objectives were drawn: To ascertain the exports competitiveness of live plants and flower-raising products from Ceará and Brazil from 1998 to 2004; to identify the existence of inducement policies for producing and commercializing live plants and flower-raising products; to identify the level of competitiveness of the exports of live plants and flower-raising products from Ceará and Brazil towards the main international exporters. The analysis was based inthe concept of competitiveness as: The capacity of a country/corporation to remain inthe market through a competitive position, created to a product or a group of products, which is the result of strategies which are able to maintain or elevate the competitive position in the international market. The methodology used was based in the descriptive tabular analysis and in the calculation of export development indicators: Revealed Comparative Advantage (RCA); Covering Tax (CT); Commerce Intensity; Exports Performance; Relative Position of Exports and Constant Market Share (CMS). The results show that the state of Ceará, during the time explored, was only competitive in the international commerce of live plants and flower-raising products in the year 2004, when it presented both RCA and CT, indicating that in this year the state presented commercial efficiency. Through the CMS model, we realized that according to the sources of export increase, the competitive effects was responsible for the average increase in the exports of live and flower-raising products in Ceará from 1998 to 2004. Brazil, through the whole period, presented superios RCA and CT, indicating that the country is commmercially dynamic in the analyzed segment when compared to other countries exports. Through the CMS model we found that according to the sources of exports increase, the competitive effect was the major responsible for the average increase in the exports of live plants and flower-raising products during the analyzed period. The indexes revealed that Brazil was competitive in the world commerce during this study. Ceará wasn't competitive from 1998 to 2003, although in 2004, the state showed a great commercial power in this area.